The Burden of Comorbidities in Obstructive Sleep Apnea and the Pathophysiologic Mechanisms and Effects of CPAP - Victoria Sircu; Silvia-Iaroslava Colesnic; Serghei Covantsev; Olga Corlateanu; Anna Sukhotko; Cristian Popovici; Alexandru Corlateanu (Clocks & Sleep, 2023)
Micro-arousals and the repeated desaturation of oxyhemoglobin, which are typical in obstructive sleep apnea syndrome (OSAS), have adverse effects on the health of patients, leading to a wide range of complications such as cardiovascular (arterial hypertension, pulmonary hypertension, chronic heart failure, arrhythmias, myocardial infarction), cerebrovascular (strokes), metabolic (insulin resistance, obesity, diabetes mellitus, metabolic syndrome), gastrointestinal (non-alcoholic liver disease), urinary (chronic renal failure), and neuropsychiatric complications as well as a wide range of malignancies. These, in turn, have multilateral effects on familial, occupational, and social life, as well as increasing the risks of road traffic accidents and accidents at the workplace. Awareness, timely screening, and the prevention of complications play important roles in diagnosing and treating comorbid conditions. This review focuses on comorbidities in OSAS and the effect of Continuous Positive Airway Pressure (CPAP) therapy on their prognoses.